G2 Interpolation for polar surfaces. Issue 5 (2nd September 2016) - Wang, Jianzhong; Cheng, Fuhua
ABSTRACT: In this paper, we present a G 2 interpolating scheme for Polar surfaces, so that polar surfaces can be used in high precision CAD/CAM applications as well. The new scheme is Bezier crust based, i.e., the interpolating surface is generated by parametrically attaching an especially selected bi-degree 5 Bezier surface to a Catmull-Clark subdivision surface. While Bezier crust based scheme handles quad faces only, we show that through a conversion process, we can handle triangular faces in the Polar part as well. Curvature continuity of the generated limit surface of our new scheme is consistent with the corresponding Polar surface. In case of a PCCS, the generated limit surface of our new scheme is G 2 on the Polar part. GRAPHICAL ABSTRACT: